Hubungan Kepadatan Tumor Associated Macrophages CD-68 dan Karakteristik Klinikopatologi pada Karsinoma Payudara Invasif - Miko Kresna Handayani; Heni Maulani; Nursanti Apriyani (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundBreast carcinoma is the most common malignancy among women worldwide. Many factors can influence prognosis of the disease.Tumor microenvironment (TME) is enriched in highly active immune cells. Herein, tumor associated macrophages (TAM) are themost prevalent immune cells. TAM can enhance tumor progression by promoting angiogenesis, invasion and metastasis. Somestudies demonstrate that high density of macrophages infiltration associated with poor prognosis. The aim of the study is todetermine the association between TAM density and clinicopathological characteristics of breast invasive carcinoma.MethodsDescriptive study with case series design on January 1, 2015-October 31, 2017 was performed at Department of AnatomicalPathology Faculty of Medicine University of Sriwijaya/dr. Moh. Hoesin General Hospital Palembang on 48 samples invasivecarcinoma mammae subtype unspecific, and have already staining with immunohistochemistry staining ER, PR, HER-2 and Ki-67,surrogate markers. Then immunohistochemistry staining using CD-68 antibody was conduced. The association between TAMdensity and clinicopathological characteristics were analyzed by using Spearman’s Rho test.ResultsThe majority of the patient are older than 40 years of age (77.1%), with positive lymphovascular invasion (79.2%), and at the gradeIII (62.5%). Bivariate analysis between TAM CD-68+density in stromal tumor and subtype luminal A showed negative correlationmoderate significantly (r= -0.398; p=0.005) while between TAM CD-68+density in stromal tumor and subtype triple negative showedpositive correlation moderate significantly (r=0.335; p=0.020).ConclusionTAM CD-68+density in stromal tumor was significantly correlated with luminal A and triple negative subtype.